From intentional to nascent student entrepreneurs: The moderating role of university entrepreneurial offerings - Jiejie Lyu; Deborah Shepherd; Kerry Lee (Journal of Innovation & Knowledge (JIK), 2023)
Entrepreneurial intention is typically acknowledged as the foundational antecedent of entrepreneurial behaviour. However, existing conceptual and empirical studies reveal that not all entrepreneurial intentions are ultimately translated into actual behaviour, resulting in an intention-behaviour gap. The current study reviewed the existing literature pertaining to this gap and found that most of the research has examined the contingent role of individual/psychological factors, yet how environmental factors, especially the institutional proximal circles, bridge the intention-behaviour link remains scarce. By employing questionnaire data (n = 1820) collected from university students in China, this research examines the effectiveness of university entrepreneurial offerings on student entrepreneurial intention realisation. The results illustrate that, although a high engagement level in university entrepreneurship education and venture creation contexts accelerates student entrepreneurs' intention-behaviour translation, the positive effect of instrumental offerings (start-up support services) is stronger than that of entrepreneurship education offerings (entrepreneurial courses and extra-curricular activities). This research extends the application of the theory of planned behaviour to the start-up process by highlighting the entrepreneurship education and venture creation factors derived from the university milieu students are exposed to in accelerating the conversion from entrepreneurial intention to nascent start-up behaviour. It captures the association amidst the effectiveness of entrepreneurship education in aspiring student entrepreneurs' entrepreneurial learning, intention actualisation, and tangible start-up activities. These findings also draw researchers' attention to explore further the nuances of various entrepreneurial offerings in student venture creation and how to build an effective university entrepreneurial ecosystem.
Keywords: L26. M13; 650; Entrepreneurship education effectiveness; Intention-behaviour gap; Start-up behaviour; Student entrepreneurship; University entrepreneurship context